Effect of T6 Heat Treatment on the Scratch Wear Behavior of Extruded AL-12wt.%SI Alloy - Yeon-Ji Kang; Jong-Ho Kim; Jong-Il Hwang; Kee-Ahn Lee (Archives of Metallurgy and Materials, 2019)
This study investigated the effect of T6 heat treatment on the microstructure and scratch wear behavior of hypoeutectic Al-12wt.%Si alloy manufactured by extrusion. Microstructural observation identified spherical eutectic Si phases before and after the heat treatment of alloys (F, T6). Phase analysis confirmed Al matrix and Si phase as well as Al2Cu and Al3Ni, Mg2Si in both alloys. In particular, Al2Cu was finer and more evenly distributed in T6 alloy. This resulted in Vickers hardness of T6 alloy that was 2.3 times greater compared to F alloy. The scratch wear test was conducted using constant load scratch test (CLST) mode and multi-pass scratch test (MPST) mode. The scratch coefficient and worn out volume obtained by such were used to evaluate wear properties before and after heat treatment. In the case of T6 alloy, its scratch coefficient was lower than F alloy in all load ranges. After 15 repeated tests to measure worn out volume, F alloy and T6 alloy measured 1.2×10–1 mm3 and 7.8×10–2 mm3, respectively. In other words, the wear resistance of T6 alloy were confirmed to be better than those of F alloy. In addition, this study attempted to identify the microstructural factors that contribute to the better scratch wear resistance of T6 alloy and wear mechanism from surface and cross-section observations after the wear tests.